Gestational weight gain and weight loss among women with gestational diabetes mellitus. (July 2018) - Komem, Daphna; Salman, Lina; Krispin, Eyal; Arbib, Nissim; Bardin, Ron; Wiznitzer, Arnon; Hadar, Eran
Abstract: Aims: To assess the association of gestational weight gain or loss with adverse pregnancy outcome among women with gestational diabetes mellitus (GDM). Methods: Retrospective study of all women diagnosed with GDM, from July 2012 to December 2016, stratified by gestational weight change according to the institute of medicine recommendations. Primary maternal outcome was glycemic control and primary neonatal outcome was large or small for gestational age (LGA or SGA). Results: 451 women were enrolled. Total weight change was associated with poor glycemic control, cesarean delivery, polyhydramnios, higher birthweight (when above recommendations), oligohydramnios and SGA (when below recommendations). GDM-related weight change was associated with polyhydramnios, cesarean delivery, higher birthweight (when above recommendations) and lower incidence of hypertensive disorders (when below recommendations). Adjusted odds ratio for poor glucose control among those with total weight gain above recommendations was 2.194 (95% CI 1.214–3.961) vs. those within-; and 1.048 (95% CI 0.611–1.799) vs. those who gained below- recommendations. The rate of SGA or LGA was not different for those gaining below or above vs. within recommendations. Conclusion: Gestational weight gain is an important predictor of glycemic control and adverse pregnancy outcome among women with GDM – both overall and GDM-related.